Le département de langue et littérature françaises de l'Université McGill de 1853 à nos jours - Lamonde, Yvan (Université McGill - Département de langue et littérature françaises, 2013)
Keywords: Langue; Université McGill

L'université McGill a 150 ans - Gourdeau-Coté, Suzanne; Smith, André (Forces, 1971)
Keywords: Université McGill

Montréal, l'Université McGill et F. A. Trottier des Rivières - Audet, Francis-J. (Missisquoi - A Store of Memories - Missisquoi County Historical Society, 1972)
Keywords: Trottier des Rivières, F. A.; Université McGill

James McGill: A Critical Biographical Study - Macsporran, Maysie Steel (Université McGill, 1930)
Keywords: McGill, James; Université McGill

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson, William; Femmes; Université McGill

The Women's College, with Special Reference to Royal Victoria College, McGill University - Dudkiewicz, Zina (Université McGill, 1982)
Keywords: Femmes; Royal Victoria College; Université McGill

McGill and Its Story, 1821-1921 - Macmillan, Cyrus (Oxford University Press, 1921)
Keywords: Université McGill

The Origins of McGill - Maclennan, Hugh (McGill: The Story of a University, 1960)
Keywords: Université McGill

McGill: The Story of a University - Maclennan, Hugh (G. Allen and Unwin, 1960)
Keywords: Université McGill

McGill University: For the Advancement of Learning. 1801-1895 - Frost, Stanley Brice (McGill-Queen's University Press, 1980)
Keywords: Université McGill

Oldest McGill - Collard, Edgar Andrew (MacMillan of Canada, 1946)
Keywords: Université McGill

James McGill of Montreal - Frost, Stanley Brice (McGill-Queen's University Press, 1995)
Keywords: McGill, James; Université McGill

James McGill and the University of McGill College - Dawson, John William (Barnard's American Journal of Education, 1863)
Keywords: McGill, James; Université McGill

James McGill and the Origin of his University - Dawson, J. W. (s.é., 1870)
Keywords: McGill, James; Université McGill

James McGill and the Origin of his University - Dawson, John William (New Dominion Monthly, 1870)
Keywords: McGill, James; Université McGill

McGill Medicine. Vol. 2 - 1885-1936 - Hanaway, Joseph; Cruess, Richard L.; Darragh, James (McGill-Queen's University Press, 2006)
Keywords: Médecine; Université McGill

McGill Medicine. Vol. 1 - The First Half Century, 1829-1885 - Hanaway, Joseph; Cruess, Richard L. (McGill-Queen's University Press, 1996)
Keywords: Médecine; Université McGill

Law at McGill: Past, Present and Future - Frost, Stanley Brice; Johnston, David L. T. (Revue de droit de McGill / McGill Law Journal, 1981)
Keywords: Droit; Université McGill

The McGill Student Body: Past and Future Enrolment - Frost, Stanley Brice; Rosenberg, Sheila (McGill Journal of Education, 1980)
Keywords: Université McGill; Étudiants

Reminiscences of the Medical School of McGill University - Maccallum, D. C. (McGill University Magazine, 1903)
Keywords: Médecine; Université McGill

On the Past, Present, and Future of the Faculty of Medecine of McGill University; an Introductory Lecture Delivered at the Opening of the Session 1866-67 - Hall, Archibald (Canada Medical Journal and Monthly Record of Medical and Surgical Science, 1866)
Keywords: Médecine; Université McGill

The Early Days of Law Teaching at McGill - Frost, Stanley Brice (Dalhousie Law Journal, 1984)
Keywords: Droit; Université McGill

An Historical Sketch of the Medical Faculty of McGill University - Abbott, M. E. (Montreal Medical Journal, 1902)
Keywords: Médecine; Université McGill

Early American Medical Schools: the Faculty of Medicine of McGill University - Abbott, M. E. (Surgery, Gynecology and Obstetrics, 1935)
Keywords: Médecine; Université McGill

The Four Founders - Quinn, R. W. (McGill Medical Undergraduate Journal, 1936)
Keywords: Médecine; Université McGill

Influence of the Edinburgh Medical School on the Early Development of McGill University - Ewing, Maurice (Journal canadien de chirurgie / Canadian Journal of Surgery, 1975)
Keywords: Médecine; Université McGill

The History of Canadian Medical Schools, VIII: McGill University, Medical Faculty - Johnson, George R. (Calgary Associate Clinic Historical Bulletin, 1949)
Keywords: Médecine; Université McGill

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

Les transformations des universités du XIIIe au XXIe siècle - Gingras, Yves; Roy, Lyse (Presses de l'Université du Québec, 2006)
Keywords: Université McGill; Université de Montréal

John William Dawson: Faith, Hope, and Science - Sheets-Pyenson, Susan (McGill-Queen's University Press, 1996)
Keywords: Dawson, William; Université McGill

Le QI de Montréal. Quartier de l'innovation ou quartier imaginaire - Shearmur, Richard (Montréal : la cité des cités, 2017)
Keywords: Griffintown; Quartiers; Université McGill

The Life of Sir William Osler - Cushing, Harvey W. (Oxford University Press, 1940)
Keywords: Médecine; Osler, William; Université McGill

The Life of Sir William Osler - Cushing, Harvey W. (Clarendon Press, 1925)
Keywords: Médecine; Osler, William; Université McGill

Histoire de la médecine au Québec, 1800-2000. De l'art de soigner à l'art de guérir - Goulet, Denis; Gagnon, Robert (Septentrion, 2014)
Keywords: Hôpitaux; Médecine; Université McGill; Université de Montréal

A Semicentennial Celebration. Introductory Address: A Sketch of the Life of the Late G.W. Campbell, A.M., M.D., L.L.D., Late Dean of the Medical Faculty, and a Summary of the History of the Faculty - Howard, R. P. (Gazette Printing, 1882)
Keywords: Campbell, George William; Médecine; Université McGill

A Biographical Sketch of the Late A.F. Holmes, M.D., LL.D., Including a Summary History of Medical Department of McGill College - Hall, Archibald (University Medical Students' Association of McGill College, 1860)
Keywords: Holmes, Andrew Fernando; Médecine; Université McGill

Andrew F. Holmes, M.D., LL.D., 1797-1860 - Abbott, M. E. (McGill University Magazine, 1905)
Keywords: Holmes, Andrew Fernando; Médecine; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
Keywords: Criminalité; Médecine; Université McGill; Étudiants

La Chambre des arts et manufactures: les quinze premières années (1857-1872) - Sabourin, Hélène (Université du Québec à Montréal, 1989)
Keywords: Board of Trade; Mechanics' Institute; Université McGill

L'institution royale et la fondation McGill - Audet, Louis-Philippe (La revue de l'Université Laval, 1952)
Keywords: Royal Institution for the Advancement of Learning; Université McGill

Eastern Gate and Western Cavalcade - a Commentory on the Part Played by Men of the Montreal General Hospital and McGill Medical School in the Early Medical History of Western Canada - Scarlett, E. P. (Canadian Services Medical Journal, 1956)
Keywords: Hôpitaux; Montreal General Hospital; Médecine; Université McGill

Andrew Fernando Holmes: Protestantism, Medicine, and Science in Nineteenth-Century Montreal - Vaudry, Richard W. (University of Toronto Press, 2020)
Keywords: Holmes, Andrew Fernando; Médecine; Protestants; Université McGill

Origines géographiques et lieux de pratique des diplômés en médecine au Québec de 1834 à 1939 - Weisz, George (Sciences et médecine au Québec. Perspectives socio-historiques, 1987)
Keywords: Anglophones; Francophones; Médecine; Université McGill; Université de Montréal; École de médecine

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Keywords: McEachran, Duncan McNab; Université McGill; École de médecine vétérinaire

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald, William C.; Philanthropie; Tabac; Université McGill

Déploiement et influence de l'Église catholique montréalaise - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Diocèse; Institut canadien; Notre-Dame (paroisse); Sulpiciens; Ultramontains; Université McGill; Université de Laval à Montréal; Églises

The Spread and Influence of the Catholic Church in Montreal - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Communautés religieuses; Diocèse; Institut canadien; Notre-Dame (paroisse); Sulpiciens; Ultramontains; Université McGill; Université de Laval à Montréal; Églises

Prehistoric Montreal - Lighthall, W. D. (Université McGill, 1920)
Keywords: Archéologie; Autochtones; Dawson, William; Hochelaga; Lighthall, William Douw

Scolarisation, industrialisation et urbanisation au XIXe siècle - Gagnon, Robert (Histoire de Montréal et de sa région, 2012)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Communautés religieuses; Enseignants; Université McGill; École normale Jacques-Cartier; École polytechnique; Écoles normales

Education in the Nineteenth Century - Gagnon, Robert (Montreal: The History of A North American City, 2018)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Communautés religieuses; Enseignants; Université McGill; École normale Jacques-Cartier; École polytechnique; Écoles normales

The Segregated City: Class and Occupation in Montreal 1861-1901/La ville différenciée: professions et classes sociales à Montréal, 1861-1901 - Lewis, Robert D. (Université McGill, Département de géographie, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The Layered City: A Revolution in Housing in Mid-Nineteenth-Century Montreal - Hanna, David B. (Université McGill, Département de géographie, 1986)
Keywords: Logement

Infant Mortality in Montreal in 1860: The Roles of Culture, Class and Habitat - Thornton, Patricia; Olson, Sherry; Thach, Quoc Thuy (Université McGill, Département de géographie,, 1987)
Keywords: Enfants; Mortalité

A Study of the Garrison Families in Montreal and Quebec City, 1855-1865 - Duchesne, André (Université McGill, Département de géographie, 1990)
Keywords: Famille; Garnison

Classe sociale et mobilité résidentielle: le cas des Irlandais à Montréal de 1851 à 1871 / Social Class and Residential Mobility, the Case of the Irish in Montreal 1851 to 1871 - Thach, Quoc Thuy (Université McGill, Département de géographie, 1985)
Keywords: Irlandais; Mobilité résidentielle

A City of Tenants: Home-Ownership and Social Class in Montreal, 1847-1881/Une ville de locataires : propriété résidentielle et classes sociales à Montréal de 1847 à 1881 - Hertzog, Stephen (Université McGill, Departement de géographie, 1985)
Keywords: Locataires; Logement

The McTavish Pumphouse - Maffini, Giulio (Université McGill, 1970)
Keywords: Aqueduc; Mont Royal

Eating in the City: Diet and Provisioning in Early Nineteenth Century Montreal - Fyson, Donald William (Université McGill, 1989)
Keywords: Alimentation

For the Benefit of the Master: the Montreal Needle Trades During the Transition, 1820-1842 - Poutanen, Mary Anne (Université McGill, 1986)
Keywords: Apprentissage; Confection; Femmes

Édouard-Raymond Fabre, bourgeois patriote du Bas-Canada, 1799-1854 - Roy, Jean-Louis (Université McGill, 1972)
Keywords: Fabre, Édouard-Raymond; Librairie; Maires; Rébellions

An Index to Retail Market Prices in Montreal 1843-1867 - Horovitz, William Bela (Université McGill, 1967)
Keywords: Prix

The Application of Steam Navigation to the St. Lawrence 1809-1840 - Wilson, George H. (Université McGill, 1961)
Keywords: Navigation; Énergie hydraulique

The Montreal Ship Channel, 1805-1865 - Corley, Nora (Université McGill, 1961)
Keywords: Navigation

Internal Dynamics and the International Cycle: Questions of the Transition in Montreal, 1821-1828 - Sweeny, Robert (Université McGill, 1985)
Keywords: Artisans; Banque de Montréal; Banques; Bourgeoisie; Hommes d'affaires; Marchands

A Fragile Authority: Power and the Religious Life in the Congrégation de Notre-Dame of Montreal, 1693-1796 - Gray, Colleen Allyn (Université McGill, 2004)
Keywords: Congrégation de Notre-Dame

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

The Cholera Epidemic of 1832: State Formation and the Origins of the Montreal Board of Health - Sendzik, Walter (Université McGill, 1997)
Keywords: Choléra; Épidémies

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Le personnage de Julie Bruneau dans la correspondance de Papineau - Arbach, Marla (Université McGill, 2001)
Keywords: Papineau, Louis-Joseph

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Intersecting Discourses: Deaf Institutions and Communities in Montreal, 1850-1920 - Perreault, Stéphane- D (Université McGill, 2003)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourdes-muettes; Institution des sourds-muets; Soeurs de la Providence; Sourds

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

'Justice in the Premises': Family Violence and the Law in Montreal, 1825-1850 - Pilarczyk, Ian C. (Université McGill, 2003)
Keywords: Criminalité; Droit; Enfants; Famille

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

The Montreal Maternity, 1843-1926: Evolution of a Hospital - Kenneally, Rhona (Université McGill, 1983)
Keywords: Hôpitaux; Montreal Maternity Hospital

The Segregated City: Residential Differentiation, Rent and Income in Montreal, 1861-1901 - Lewis, Robert D. (Université McGill, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The Presbyterian College Montreal, 1865-1915 - Johnston, John A. (Université McGill, 1951)
Keywords: Presbyterian College; Presbytériens; Protestants

The Irish Migration to Montreal, 1847-1867 - Keep, George Rex (Université McGill, 1948)
Keywords: Irlandais

Socio-Spatial Patterns of Infant Survival in Montreal, 1859-1860 - Thach, Quoc Thuy (Université McGill, 1987)
Keywords: Enfants; Mortalité

The First Fifteen Years of British Administration in Montreal, 1760 to 1775 - Dewey, Alex G. (Université McGill, 1913)
Keywords: Britanniques

The American Presbyterian Church of Montreal, 1822-1866 - Knowles, David Clifford (Université McGill, 1957)
Keywords: American Presbyterian Church; Presbytériens; Protestants

Farm Leases and Agriculture on the Island of Montreal, 1780-1820 - Waywell, Jennifer L. (Université McGill, 1989)
Keywords: Baux à ferme; Notaires

A Stake in the System: Domestic Property Ownership and Social Class in Montreal, 1847-1881 - Hertzog, Stephen (Université McGill, 1984)
Keywords: Logement

La Banque du Peuple, 1835-1871, and its Failure, 1895 - Greenfield, Robert S. (Université McGill, 1968)
Keywords: Banque du Peuple; Banques

A History of St. John's School and Lower Canada College - Caverhill, Austin (Université McGill, 1961)
Keywords: Lower Canada College; St. John's School

The Legal Rights of Masters, Mistresses and Domestic Servants in Montreal, 1816-1829 - Hogg, Grace Laing (Université McGill, 1989)
Keywords: Domestiques; Femmes

History of the Theatre in Montreal Prior to the Confederation - Conroy, Patricia (Université McGill, 1936)
Keywords: Théâtre

The Civil Architecture of John Ostell - James, Ellen S. (Université McGill, 1983)
Keywords: Arpenteurs; Ostell, John

The Montreal Villa, 1830 to 1930 - Jooste, Johan K. (Université McGill, 1985)

An Imperial Garrison in its Colonial Setting. British Regulars in Montreal, 1832-1854 - Senior, Elinor Kyte (Université McGill, 1976)
Keywords: Armée; Britanniques; Garnison

The Annexation Movement of 1849-50 as Seen through the Lower Canadian Press - Mills, G. H. S. (Université McGill, 1947)
Keywords: Avenir (L'); Minerve (La); Montreal Gazette; Mouvement annexionniste

The First Incorporation of the City of Montreal, 1826-1836 - Ste Croix, Lorne (Université McGill, 1971)

Paupérisme et assistance sociale à Montréal 1832-1865 - Lapointe-Roy, Huguette (Université McGill, 1972)
Keywords: Pauvreté

Abandoned Children in Nineteenth-Century Montreal - Gossage, Peter (Université McGill, 1984)
Keywords: Communautés religieuses; Crèche d'Youville; Enfants; Orphelinats; Soeurs Grises

L'Institut canadien de Montréal 1844-1883: le contenu littéraire de la bibliothèque - Lebeau, Armande (Université McGill, 1981)
Keywords: Institut canadien

Early Canadian Historical Literature: The Journal of the Traders of the North West Co. Of Merchants from Canada - O'Brien, M. V. (Université McGill, 1957)
Keywords: Compagnie du Nord-Ouest; Fourrure; Marchands

Montreal's Musical Life Under the Union, with an Emphasis on the Terminal Years, 1841 and 1867 - Slemon, Peter (Université McGill, 1976)
Keywords: Musique

L'éducation dans le diocèse de Montréal d'après la correspondance de ses deux premiers évêques, Mgr J.-J. Lartigue et Mgr I. Bourget, de 1820 à 1867 - Majerus, Yvette-Viviane (Université McGill, 1971)
Keywords: Bourget, Ignace; Lartigue, Jean-Jacques; Évêques

The Lachine Canal - Cureton, Edward A. (Université McGill, 1957)
Keywords: Lachine (canal); Navigation

The Construction of the First Lachine Canal, 1815-1826 - Tulchinsky, Gerald (Université McGill, 1960)
Keywords: Lachine (canal); Navigation

Montreal Up in Smoke: A Spatial Analysis of Mid-Nineteenth Century Urban Fires - Spencer, Pheobe (Université McGill, 2011)
Keywords: Incendies

Madame James McGill (1747-1818): Marie-Charlotte Guillimin, ou, La vie d'une femme mondaine à Montréal au dix-huitième siècle - Tanguay, Lynda (Université McGill, 1993)
Keywords: Bourgeoisie; McGill, James

The Law of Servants and the Servants of the Law: Judicial Regulation of Labour Relations in Montreal, 1830-1845 - Pilarczyk, Ian C. (Université McGill, 1997)
Keywords: Droit; Travail

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

God's Mobile Mansions: Protestant Church Relocation and Extension in Montreal, 1850-1914 - Trigger, Rosalyn (Université McGill, 2004)
Keywords: Protestants; Églises

Human Scale in the Urban Design of Montreal Residential Developments - Lucic, Katija (Université McGill, 1995)
Keywords: Anjou; Banlieue; Centre-sud (quartier); Quartiers; Rues; Squares

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)

Joseph Gould and the Montreal Mendelssohn Choir - Rice, Kelly Stanley (Université McGill, 1991)
Keywords: Musique

Les troubles de 1860-1880 à Oka: choc de deux cultures - Pariseau, Claude L. (Université McGill, 1975)
Keywords: Autochtones; Communautés religieuses; Sulpiciens

L'histoire par l'image: commémoration picturale, pouvoir politique et stratégies visuelles au Québec (1880-1930) - Roy, Nathalie Anne (Université McGill, 2005)

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

Privacy in Row Houses of Montreal - Rahbar, Mehrdad (Université McGill, 1996)
Keywords: Logement

Secular and Parochial Education of Ashkenazi and Sephardi Jewish Children in Montreal: A Study in Ethnicity - Hirschberg, Jack Jacob (Université McGill, 1988)
Keywords: Enfants; Juifs

Shifting Cultures of Recycled Style: A History of Second-Hand Clothing Markets in Montreal - Diggins, Kimberly A. (Université McGill, 1998)
Keywords: Vêtements

The Changing Character of Streets in Central Areas with Special Reference to Sherbrooke Street as a Principal Street in City of Montreal-Canada - Rege, Ratan M. (Université McGill, 1966)
Keywords: Rues; Sherbrooke (rue)

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

The Royal Institution for the Advancement of Learning: The Correspondence, 1820-1829, a Historical and Analytical Study - Boulianne, Réal G. (Université McGill, 1970)
Keywords: Royal Institution for the Advancement of Learning

The American Element in the Early Presbyterian Church in Montreal, 1786-1824 - Mcdougall, Elizabeth Ann (Université McGill, 1965)
Keywords: Presbytériens; Protestants; St Gabriel Street Presbyterian Church; St. Andrew and St. Paul (église); Églises

Authoritarianism, Constitutionalism and the Special Council of Lower Canada, 1838-1841 - Watt, Steven (Université McGill, 1998)
Keywords: Association constitutionnelle de Montréal (MCA); Loyalistes; Rébellions

An Account of English Journalism in Canada from the Middle of the Eighteenth Century to the Beginning of the Twentieth, with Special Emphasis Being Given to the Periods Prior to Confederation - Read, S. M. E. (Université McGill, 1925)
Keywords: Anglophones; Gazette Littéraire de Montréal; Minerve (La); Montreal Gazette; Montreal Herald; Montreal Witness

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

Development of Cote A Baron - Marshall, Robert S. (Université McGill, 1983)
Keywords: Baron (côte à)

Imported Devotions: Roman Catacomb Saints in Ultramontane Montreal - Dahan, Michel (Université McGill, 2014)
Keywords: Reliques; Ultramontains; Églises

A Community of Believers and Healers: Learning from the functional characteristics of Hôtel Dieu - McDonald, Marie-Pierre (Université McGill, 2014)
Keywords: Communautés religieuses; Hôpitaux; Hôtel-Dieu

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

The Irish in the Province of Canada in the Decade Leading to Confederation - Lyne, Daniel Colman (Université McGill, 1960)
Keywords: Irlandais

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Upper Class Reaction to Poverty in Mid-Nineteenth Century Montreal: A Protestant Example - Harvey, Janice (Université McGill, 1978)
Keywords: Pauvreté; Protestants

The Role of the Parish in Fostering Irish-Catholic Identity in Nineteenth-Century Montreal - Trigger, Rosalyn (Université McGill, 1997)
Keywords: Irlandais; Notre-Dame (paroisse)

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith, Donald

The many worlds of Louis Riel: a political odyssey from Red River to Montreal and back 1840-1875 - Hamon, Max (Université McGill, 2017)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman, William; Photographie

Settling an 18th Century Faubourg: Property and Family in the Saint-Laurent Suburb, 1735-1810 - Stewart, Alan M. (Université McGill, 1988)
Keywords: Famille; Faubourgs; Quartiers; Saint-Laurent (quartier)

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Honnêtes hommes et gentilshommes : L'éducation classique des garçons et la formation du soi masculin au Bas-Canada à l’âge des révolutions (1791-1840) - McCutcheon, Shawn (Université McGill, 2021)
Keywords: Collèges classiques

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman, William; Photographie; Écossais

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage